2021
DOI: 10.1111/plb.13296
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous melatonin‐mediated regulation of K+/Na+ transport, H+‐ATPase activity and enzymatic antioxidative defence operate through endogenous hydrogen sulphide signalling in NaCl‐stressed tomato seedling roots

Abstract: Melatonin (Mel) and hydrogen sulphide (H2S) have emerged as potential regulators of plant metabolism during abiotic stress. Presence of excess NaCl in the soil is one of the main causes of reduced crop productivity worldwide. The present investigation examines the role of exogenous Mel and endogenous H2S in tomato seedlings grown under NaCl stress. Effect of 30 µm Mel on endogenous synthesis of H2S was examined in roots of NaCl‐stressed (200 mm) tomato seedlings. Also, the impact of treatments on the oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…It was also shown that H 2 S plays a vital role in enhancing plant tolerance to abiotic stress and alleviating its detrimental effects [ 89 , 90 , 91 , 92 ]. Melatonin increased the activities of the H 2 S-produced enzymes ( D -cysteine desulfhydrase (DCD), L -cysteine desulfhydrase (LCD)), thus improving H 2 S accumulation [ 93 , 94 , 95 ]. Further, application of hypotaurine (HT, H 2 S scavenger) reversed the contribution of melatonin in alleviation of the salinity and heat damages by reestablishing the redox homeostasis in tomato, cucumber, and wheat seedlings [ 44 , 94 , 95 ].…”
Section: Plant Abiotic Stress Tolerance Is Mediated By the Crosstalk ...mentioning
confidence: 99%
“…It was also shown that H 2 S plays a vital role in enhancing plant tolerance to abiotic stress and alleviating its detrimental effects [ 89 , 90 , 91 , 92 ]. Melatonin increased the activities of the H 2 S-produced enzymes ( D -cysteine desulfhydrase (DCD), L -cysteine desulfhydrase (LCD)), thus improving H 2 S accumulation [ 93 , 94 , 95 ]. Further, application of hypotaurine (HT, H 2 S scavenger) reversed the contribution of melatonin in alleviation of the salinity and heat damages by reestablishing the redox homeostasis in tomato, cucumber, and wheat seedlings [ 44 , 94 , 95 ].…”
Section: Plant Abiotic Stress Tolerance Is Mediated By the Crosstalk ...mentioning
confidence: 99%
“…H 2 S enhanced photosynthesis and antioxidant enzyme activity, and up-regulated the transcripts of PC genes to alleviate Cd stress in tobacco [33]. Moreover, H 2 S homeostasis and L-cysteine desulfhydrase activity were involved in melatonin-modulated salt stress tolerance in tomato and cucumber seedlings [31,34,35]. Crosstalk of melatonin and H 2 S in alleviating heat stress was also suggested in wheat [36].…”
Section: Introductionmentioning
confidence: 88%
“…Exogenous melatonin regulated the endogenous H 2 S homeostasis by modulating the L-DES activity in salt-stressed tomato cotyledons [31]. Moreover, an endogenous H 2 S-dependent pathway was involved in melatonin-mediated salt stress tolerance in tomato seedling roots [34]. Synergistic effects of melatonin and H 2 S regulated K + /Na + homeostasis, and reduced excessive accumulation of ROS by enhancing the activity of antioxidant enzymes.…”
Section: Crosstalk Of Melatonin and H 2 S In Plantsmentioning
confidence: 98%
See 2 more Smart Citations